Fever: Optimal Responsive View Synchronisation - Eranki, Varun Maitreya

Not your Average Digital Nudge: Heterogeneous Effects of Personalized Nudges with CausalML - Bösch, Kevin; Müller, Oliver; Weinmann, Markus (Proceedings of the Symposium on Statistical Challenges in Electronic Commerce Research)

Die Formierung katholischer Universitätstheologie im Königreich Preußen und der Hermesianismus - Ströhmer, Michael; Dahlke, Benjamin (Georg Hermes (1775-1831). Rationale Glaubensbegründung, theologische Konflikte und regionale Identitätsbildung im 19. Jahrhundert)

FSU als Bühne: Teatro aplicado - del Valle, Victoria (Fremdsprachendidaktik kurzgefasst)

Measuring Visual Attention Capacity Across xReality - Biermeier, Kai; Scharlau, Ingrid; Yigitbas, Enes (Proceedings of the 17th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2024))
Augmented (AR) and Virtual Reality (VR) technologies have been applied very broadly in the recent past. While prior work emphasizes the potential of these technologies in various application domains, the process of visual attention in and across the contexts of AR/VR environments is not exhaustively explored yet. By now, visual attention in AR/VR environments has majorly been studied by means of overt attention (i.e. saccadic eye movements), self-report, and process-related visual attention proxies (like reaction time). In this work, we analyze covert visual attention based on the (psychological) Theory of Visual Attention (TVA), which allows us to quantify theory-based interpretable properties of the visual attention process. For example, the TVA allows us to measure the overall processing speed. We instantiate this TVA-based framework with a 30-participant explorative within-subjects study. The results show a decisive difference in visual attention between Reality (i.e. the neutral condition) and Virtual Reality and a weak difference between Reality and Augmented Reality. We discuss the consequences of our findings and provide ideas for future studies.
Keywords: Visual Attention; TVA; Cognitive Modelling; Bayesian Modelling; AR; VR

Totgeschwiegen. Die fehlende Stellungnahme zu Lage der Jüdinnen und Juden durch die Bekennende Kirche im Nationalsozialismus - Janus, Richard

Lehrpraktiken, Sozialisation und Selektion im Sozialraum Hochschule - Steinhardt, Isabel (Hochschullehre postdigital: Lehren und Lernen neu gestalten)
Die soziale Ungleichheit im Hochschulsystem nimmt nur sehr langsam ab. Als eine Begründung gilt die Ausrichtung von Hochschulen an einem akademischen Habitus, der andere Habitus ausgrenzt und zu Passungsproblematiken führt. Wie diese Passungsproblematiken aufseiten der Studierenden entstehen ist ein mittlerweile unter suchtes Phänomen. Die Lehrenden und ihre Praktiken als zentraler Part der Lehr-Lern-Interaktion werden kaum betrachtet. Dieser Beitrag zeigt anhand einer Sekundärauswertung von zehn qualitativen Studien Praktiken des Lehrhandelns und der Interaktion zwischen Lehrenden und Studierenden auf. Analysiert wurden die Studien im Hinblick auf die Frage wie doing difference stattfindet, also wie durch Lehrpraktiken Studierende kategorisiert werden und welche Selektions- und Ausgrenzungsprozesse dadurch stattfinden. Dabei stütze ich mich auf die abgedruckten Interviewpassagen ebenso wie auf die von den Autorinnen und Autoren gemachten Analysen. Die Lehrpraktiken zeichnen sich durch eine geringe Diversitätssensibilität mit wenig Hilfsangeboten und eine starke Befürwortung von Leistungsorientierung und Selektion aus.
Keywords: Lehrpraktiken; Lehrhabitus; Fachhabitus : Selektion; Sozialisation

Professionalisierungsmöglichkeiten angehender Lehrkräfte in Praxisphasen - Rodemer, Marc; Mientus, Lukas; Wiedmann, Julia; Nowak, Anna; Pollmeier, Pascal (Frühe naturwissenschaftliche Bildung)

Entanglement-assisted quantum speedup: Beating local quantum speed limits - Yasmin, Farha; Sperling, Jan (Physical Review A)

Study on hydrodynamic and mass transfer performance of Mellapak 250Y for FPSO units exposed to permanent tilt and roll motion - Mamedov, Tural; Schleicher, Eckhard; Schubert, Markus; Holger, Kryk; Ehlert, Thomas; Kenig, Eugeny Y.; Hampel, Uwe

Politische Bildung im Sachunterricht – konzeptionelle Sichtweisen, empirische Erkenntnisse und exemplarische Lehr- und Lernprojekte - Becher, Andrea; Gläser, Eva; Kallweit, Nina (Politische Bildung im Sachunterricht Potenziale – Positionen – Perspektiven)

Politische Bildung im Sachunterricht. Potenziale – Positionen – Perspektiven

Das Forschungsprojekt „PoWi-Kids – Politisches Wissen von Kindern“ im Kontext politikdidaktischer Forschungslinien - Becher, Andrea; Gläser, Eva (Politische Bildung im Sachunterricht Potenziale – Positionen – Perspektiven)

Kriterien für barrierefreie Veranstaltungen partizipativ entwickeln - Freymuth, Nina; Weber, Elisa; Tillmann, Vera

Quantum walks and entanglement in cavity networks - Di Fidio, Christian; Ares, Laura; Sperling, Jan (Physical Review A)

Electrical trace analysis of superconducting nanowire photon-number-resolving detectors - Schapeler, Timon; Lamberty, Niklas; Hummel, Thomas; Schlue, Fabian; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Bartley, Tim (Physical Review Applied)
We apply principal component analysis (PCA) to a set of electrical output signals from a commercially available superconducting nanowire single-photon detector (SNSPD) to investigate their photon-number-resolving capability. We find that the rising edge as well as the amplitude of the electrical signal have the most dependence on photon number. Accurately measuring the rising edge while simultaneously measuring the voltage of the pulse amplitude maximizes the photon-number resolution of SNSPDs. Using an optimal basis of principal components, we show unambiguous discrimination between one- and two-photon events, as well as partial resolution up to five photons. This expands the use case of SNSPDs to photon-counting experiments, without the need of detector multiplexing architectures. Published by the American Physical Society 2024

The Transformation of the Organization of Work: Towards Community-based Forms of Work Organization - Krause, Ina; Oertel, Simon (Handbook of Organizing Economic, Evironmental and Societal Transformation.deGruyter.)

An interview with Christian Fuchs on Communication and Media Studies - Fuchs, Christian (Moment)

Topic Study Group 41: Research and development on textbooks and resources for learning and teaching mathematics - Rezat, Sebastian; Visnovska, Jana; Yan, Guorui; Leshota, Moneoang; Sabra, Hussein (Proceedings of the 14th International Congress on Mathematical Education)
Keywords: Mathematics; Mathematik; Textbook; Curriculum Resources; Schulbuch

Symmetries of power-free integers in number fields and their shift spaces - Gundlach, Fabian; Klüners, Jürgen (arXiv:2407.08438)
We describe the group of $\mathbb Z$-linear automorphisms of the ring of integers of a number field $K$ that preserve the set $V_{K,k}$ of $k$th power-free integers: every such map is the composition of a field automorphism and the multiplication by a unit. We show that those maps together with translations generate the extended symmetry group of the shift space $\mathbb D_{K,k}$ associated to $V_{K,k}$. Moreover, we show that no two such dynamical systems $\mathbb D_{K,k}$ and $\mathbb D_{L,l}$ are topologically conjugate and no one is a factor system of another. We generalize the concept of $k$th power-free integers to sieves and study the resulting admissible shift spaces.